2019
DOI: 10.1093/milmed/usz069
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Videoconference-Adapted Version of the Community Diabetes Prevention Program, and Comparison of Weight Loss With In-Person Program Delivery

Abstract: IntroductionEffective, standardized, and easily accessible weight management programs are urgently needed for military beneficiaries. Videoconference interventions have the potential for widespread scaling, and can provide both real time interaction and flexibility in delivery times regardless of location, but there is little information on their effectiveness and acceptability.Materials and MethodsThis study as part of a larger weight loss trial describes the videoconference adaption of Group Lifestyle Balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
(21 reference statements)
2
16
0
3
Order By: Relevance
“…The present study is the first to show that an intensive multimodal weight loss intervention for morbid obesity can induce a 12-month weight loss greater than 20%, whether delivered face to face or partially remotely. This is in line with previous reports that found weight loss after standard behavioral treatment comparable between inperson, phone-, or videoconferencing delivery [7,[14][15][16][17] and confirms that delivery mode might not be a significant predictor of 12-month weight loss [6].…”
Section: Weight Losssupporting
confidence: 92%
“…The present study is the first to show that an intensive multimodal weight loss intervention for morbid obesity can induce a 12-month weight loss greater than 20%, whether delivered face to face or partially remotely. This is in line with previous reports that found weight loss after standard behavioral treatment comparable between inperson, phone-, or videoconferencing delivery [7,[14][15][16][17] and confirms that delivery mode might not be a significant predictor of 12-month weight loss [6].…”
Section: Weight Losssupporting
confidence: 92%
“…Several large clinical trials have shown similar outcomes for programs using group telephone calls versus face-to-face groups (4,5), and one fully powered equivalency trial demonstrated no difference in outcomes between these modalities (6). To date, only smaller pilot studies have implemented group-based interventions via newer videoconferencing technology (7)(8)(9); however, results have demonstrated weight losses smaller in magnitude (e.g., 4%-5% from baseline weight) than traditional in-person interventions.…”
mentioning
confidence: 99%
“…By decreasing the time and resource commitments needed for frequent counseling appointments, telemedicine may also help improve long‐term adherence. In one study, a comparison between patients who participated in a weight‐loss intervention visit via videoconference and those who attended in person showed a significantly higher retention rate (96%) for those who participated by videoconference compared with those who attended in person (70%) (46). In a fully online, medically monitored weight‐management program, Alencar et al (51) investigated whether weekly health coaching delivered via videoconferencing could increase adherence to the use of remote‐monitoring devices (scale and tracker).…”
Section: Opportunities For Telemedicine To Address Several Key Barrie...mentioning
confidence: 99%
“…Telemedicine has also been utilized to improve access to obesity treatment for patients who are active-duty members of the military, military families (46), and veterans (36,47). A retrospective cohort study evaluated the effectiveness of providing a weight-management program to veterans via videoconferencing.…”
Section: Specific Interventions Have Been Developed For Certain Commu-mentioning
confidence: 99%
See 1 more Smart Citation